Moving Forward towards Rural Economic Transformation - Acharya, Gayatri (World Bank, Washington, DC, 2020)
Overview of implementation experience and progress: the first phase of the National Rural Livelihoods Project (NRLP), which aimed to reach 4.8 million rural women, was implemented across 13 states, 162 districts and 580 blocks of the country. NRLP was meant to support the launch and expansion of the Government of India’s flagship program for poverty alleviation, the Deendayal Antyodaya Yojana National Rural Livelihood Mission (DAY-NRLM) and provide additional pro-poor investments in 13 states with the highest poverty rates which accounted for almost 85 percent of the poor in India. This program marked a strategic shift within the Ministry of Rural Development (MoRD) from a focus on allocation, disbursement, and monitoring of central government financial resources, to the provision of skilled technical assistance to states under the aegis of the DAY-NRLM.